Voluntary Standard Systems
XVI, 459 p. 40 illus.
Keywords: Emerging to the forefront of sustainable production and consumption are a promising and rapidly evolving concept known as Voluntary Standard Systems (VSS). They encompass the three pillars of sustainability – social, environmental and economic aspects, and consequently they can be considered as a tool, which makes sustainable development visible. Currently, they are becoming a significant element in international trade and in the promotion of sustainable development strategies, especially in the context of globalised markets and supply chains. This volume provides a comprehensive overview of the current VSS concepts: from their nature and functioning, to the future outlook for their development. It places VSS in the broader context of global development issues and challenges, including development policy and international sustainability commitments, progress towards achieving ‘green economy’, and meeting climate protection targets. The volume contains also a representative selection of case studies which demonstrate their wide range of application in different sectors of the economy.